El pensamiento sistémico como herramienta para el desarrollo de competencias ciudadanas (2019)
Over time, Colombia has been considered a violent and corrupt country according to different international statistics (Berrocal, 2017). Therefore, the formation of citizenship has become a challenge so that democratic participation, a construction for peace and the implementation of respect for plurality can be exercised (Zarate, 2010). The MEN with the purpose of improving citizenship training, has implemented a Program of Citizen Competencies in educational establishments, but according to Castro (2014) this only reaches corrective and non-formative ends. That is why, at present, it is important to carry out research that aims to identify the factors associated with the development of Citizen Competencies, therefore, it is up to education to be an instrument that helps facilitate and improve that aspect. For this reason, this degree project aimed to evaluate Systemic Thinking as a support tool for the development of Citizen Competences and was based on a mixed approach, which involved four phases: the first was a literary investigation in which It related the concepts of Systemic Thinking and Citizen Competences, the second and the third were based on the characterization of the training processes of the Citizen Competences of both the colleges linked to the university and those of the university itself and the fourth phase was the Analysis of the results of the Saber Pro Tests of the component of Systemic Thinking in the module of the Citizen Competencies of Engineering. As a final result, it was obtained that Systemic Thinking and Citizenship Competencies have a relationship based on four aspects: a global vision, an integrating part, a transversality in education and in Pro Saber Pro tests. On the other hand, it was found that of the formative processes of the Citizen Competences of the colleges linked to the university and of the same, the Systemic Thinking is present implicitly within the development of their classes, and, finally, it was affirmed that there are no significant differences of the scores of those Engineering careers that do see Systemic Thinking within their classroom plan versus those who do not see it. Finally, it can be said that Systemic Thinking is a discipline transversal to all areas of knowledge, which allows a holistic view of social reality, also helps to exercise cognitive, emotional, communicative and integrative skills through the five disciplines being this one of them, managing to make coherent decisions for the solution of society's problems, with which it can be concluded that it is a good ally for the strengthening of Citizen Competencies